Changing relative intrinsic growth rates of species alter the stability of species communities - Löffler, Thomas J.; Lischke, Heike (Frontiers in Ecology and Evolution, 2023)
It is perplexing when species-rich ecosystems change abruptly and, for example, dominant or economically interesting species populations collapse. Although various aspects of such ecosystem regime shift at tipping points have been studied, little attention has been paid to the possible dependence of community stability on the intrinsic growth rates of their species. Intrinsic growth rates of species can vary, e.g., due to evolution, environmental changes or fluctuations, disturbances, or human influences such as exploitation of certain species. We show theoretically and computationally that under certain conditions changing relative intrinsic growth rates of competing species have a strong effect on community stability. In addition, we are investigating which species characteristics favour such changes of communities from stable to unstable and vice versa. This is a provisional file, not the final typeset article common approach is to analyze the effects of species characteristics of these LV models on the stability of equilibria that reflect the community composition in terms of species identities and abundances. These characteristics, e.g., the intrinsic growth rates, are assumed to depend on the environment. Many studies of LV models focused on the influence of interaction parameters (